Reliability in the Ability to Self-regulate Sprint Intensity in Male Professional Soccer Players - Acena Rodriguez, A.; Gonzalez Figuerola, A. A. (American Journal of Sports Science, 2022)
According with the purpose of this study, 15 professional male soccer players were recruited, and the sprint Vmax of 30 m were measured in partials of 60%, 70%, 80%, 90%, and 100% intensity, using Global Positioning Systems devices (GPS). The protocol of measurements was 2 days of testing separated by a week. The order was randomized both in the subjects and in the execution intensities. The statistical analysis was performed using Student's T-test for paired data, and a repeated measures ANOVA. Changes in Vmax were observed when it was requested to vary the intensity by 10% (p<0.05). Without precision (p <0.05) in the partials 60%, 70%, and 80%, the speed was higher than requested (65.66% ± 5.64%, 74.65% ± 5.84%, and 86.1% + 4.3% of Vmax), while in the partial 90% (87.93% ± 5.81%) the speed was similar to that requested (p> 0.05) although slightly lower. In conclusion, professional soccer players are capable of varying speed when a change in intensity is verbally requested, but without precision and exceeding the indicated intensity, except for intensities close to Vmax 90%), which are precise although slightly lower. According with the results of this research, the use of objective feedback methods may be necessary, when planning speed running close to submaximal speed.